Insights into the Unexpected Chemoselectivity for the N‑Heterocyclic Carbene-Catalyzed Annulation Reaction of Allenals with Chalcones - Qiao, Yan; Wei, Donghui; Chang, Junbiao (Journal of organic chemistry, 2015)
Lewis base N-heterocyclic carbene (NHC)-catalyzed annulation is the subject of extensive interest in synthetic chemistry, but the reaction mechanisms, especially the unexpected chemoselectivity of some of these reactions, are poorly understood. In this work, a systematic theoretical calculation has been performed on NHC-catalyzed annulation between allenals and chalcone. Multiple possible reaction pathways (A–E) leading to three different products have been characterized. The calculated results reveal that NHC is more likely to initiate the reaction by nucleophilic attack on the center carbon atom of the allene group but not the carbonyl carbon atom in allenals leading to the Breslow intermediate, which is remarkably different from the other NHC-catalyzed annulations of unsaturated aldehydes with chalcones. The computed energy profiles demonstrate that the most energetically favorable pathway (A) results in polysubstituted pyranyl aldehydes, which reasonably explains the observed chemoselectivity in the experiment. The observed chemoselectivity is demonstrated to be thermodynamically but not kinetically controlled, and the stability of the Breslow intermediate is the key for the possibility of homoenolate pathway D and enolate pathway E. This work can improve our understanding of the multiple competing pathways for NHC-catalyzed annulation reactions of unsaturated aldehydes with chalcones and provide valuable insights for predicting the chemoselectivity for this kind of reaction.